2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-1138
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete and Distributed Steady Blowing Application on a High Reynolds Number Semispan Supercritical Wing Configuration

Abstract: The FAST-MAC circulation control model was modified to test an array of steady and unsteady actuators at realistic flight Reynolds numbers in the National Transonic Facility at the NASA Langley Research Center. Previous experiments in the FAST-MAC test series used a fullspan tapered slot, and that configuration is used as a baseline for performance and weight flow requirements. The goal of the latest experiment was to reduce the weight flow required to achieve comparable performance established by the baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Over the last decade, aerospace organizations such as NASA, DLR, Boeing and the European consortium AFLoNext, have conducted studies on this subject as shown in the works by Bushnell and Wygnanski (2020), Lin et al (2019), Melton et al (2018), Jones et al (2018), Delfs et al (2017), Ciobaca and Wild (2013), DeSalvo et al (2020), Shmilovich et al (2018), Rosenblum et al (2019), Wild (2020) and Hue et al (2017). These authors show that Active Flow Control mechanisms are able to manipulate the fluid flow field from its natural state to a desired state.…”
Section: Overviewmentioning
confidence: 98%
“…Over the last decade, aerospace organizations such as NASA, DLR, Boeing and the European consortium AFLoNext, have conducted studies on this subject as shown in the works by Bushnell and Wygnanski (2020), Lin et al (2019), Melton et al (2018), Jones et al (2018), Delfs et al (2017), Ciobaca and Wild (2013), DeSalvo et al (2020), Shmilovich et al (2018), Rosenblum et al (2019), Wild (2020) and Hue et al (2017). These authors show that Active Flow Control mechanisms are able to manipulate the fluid flow field from its natural state to a desired state.…”
Section: Overviewmentioning
confidence: 98%